A randomized DBPC trial to determine the optimal effective and safe dose of a SLIT‐birch pollen extract for the treatment of allergic rhinitis: results of a phase II study. Issue 1 (26th October 2015) - Pfaar, O.; van Twuijver, E.; Boot, J. D.; Opstelten, D. J. E.; Klimek, L.; van Ree, R.; Diamant, Z.; Kuna, P.; Panzner, P.
Abstract: Background: Sublingual immunotherapy (SLIT) is a potential efficacious and safe treatment option for patients with respiratory, IgE‐mediated allergic diseases. A combined tolerability, dose‐finding study with a sublingual liquid birch pollen preparation (SB) was conducted. Methods: Two hundred and sixty‐nine adults with birch‐pollen‐induced AR were randomized to placebo, SB: 3333, 10 000, 20 000 or 40 000 AUN/ml. Differences in symptom scores following a titrated nasal provocation test (TNPT) at baseline and after 5 months of treatment were determined. Safety, tolerability, birch‐pollen‐specific immunoglobulin levels and peak nasal inspiratory flow (PNIF) were also measured (all measures determined outside the birch pollen season). Results: In all treatment groups, an improvement in symptom scores after treatment compared to baseline was observed, with an additional stepwise improvement in the active groups compared to placebo, which was significant in high‐dose groups ( P = 0.008 and P < 0.001, respectively). For this primary endpoint, a significant linear dose–response curve was observed: the higher the dose, the better the improvement observed. Likewise, active treatment resulted in an increase in PNIF and serum IgG levels compared to placebo. The highest improvements were found in the 40 000 AUN/ml group. All active dosages resulted in more adverse reactions than placebo, which were mainly mild and well‐controlled. Conclusions: A multicentre trial evaluated the dose–response and tolerability of SB. All active treatment groups showed better responses than placebo for both primary and secondary parameters. The results indicate that, within the studied dose range, SB 40 000 AUN/ml is the most optimal effective and safe dose (ClinicalTrials.gov: NCT01639768).